Zeolite application and irrigation during ripening reduced berry sunburn damage and yield loss in cv. Sangiovese (Vitis vinifera L.) - Allegro, Gianluca; Valentini, Gabriele; Sangiorgio, Daniela; Pastore, Chiara; Filippetti, Ilaria (Frontiers in Plant Science, 2024)
Climate change poses significant challenges to the grapevine cultivation for wine production. In the last years, the occurrence of extreme weather events such as intense heat waves and prolonged period of drought increased sunburn damage with negative consequences to yield and berry composition. Short-term adaptation strategies are urgently needed to mitigate these effects. In this light, our study aimed to evaluate the efficacy of zeolite application on the canopy and irrigation during ripening on sunburn damage, yield and berry composition in cv. Sangiovese (Vitis vinifera L.). Over three years (2021-2023), canopy management and irrigation treatments were arranged in a strip-plot design. Canopy management treatments included leaf removal on the cluster zone, with and without zeolite application, and no defoliated control; irrigation treatments comprised irrigation from berry softening and no irrigation. Both zeolite application and irrigation reduced sunburn damage, thus mitigating yield loss. Regarding berry composition, zeolite application did not alter the main parameters, while irrigation led to reductions in sugar and anthocyanin concentrations. These findings suggest that zeolite application and irrigation during ripening represent promising and cost-effective solutions for grape growers facing climate change-induced challenges. However, further studies are necessary to optimize timing of irrigation to avoid detrimental effects on anthocyanin accumulation.